Effect of Locally Delivered Melatonin as an Adjunct to Nonsurgical Therapy on GCF Antioxidant Capacity and MMP-9 in Stage II Periodontitis Patients: A Randomized Controlled Clinical Trial - Enji Ahmed; Olfat G. Shaker; Nermin Yussif; Dalia M. Ghalwash (International Journal of Dentistry)
Objectives. Periodontitis is characterized by inflammatory destruction of periodontal tissue, loss of attachment, and bone resorption. The increase in reactive oxygen species (ROS) is responsible for the oxidative damage occurring in periodontal tissues. Melatonin has important immunomodulatory, anti-inflammatory, and powerful antioxidant functions. The current study was carried out to evaluate the effect of topical melatonin gel as an adjunct to nonsurgical periodontal therapy. Methods. This split-mouth randomized controlled clinical trial was performed on 24 patients with grade II periodontitis. Two sites in each patient were randomly assigned; test sites were treated by nonsurgical therapy followed by intrapocket application of 5% melatonin gel. Control sites were treated by nonsurgical therapy followed by intrapocket application of placebo gel. Both the melatonin and placebo gel were applied weekly once for four weeks. Assessment of clinical parameters (PD and CAL) was done at baseline and 3 months after therapy. Total antioxidative capacity (TAC) and matrix metalloproteinase-9 (MMP-9) levels in GCF were also evaluated utilizing commercially available enzyme-linked immunosorbent assay kits (ELISA) at baseline and 3 months after therapy. Results. Treatment with topical melatonin was associated with a reduction in periodontal inflammation reflected as an improvement in the clinical periodontal parameters. Melatonin-treated sites showed a more statistically significant percent reduction in PD and more statistically significant percent gain in CAL than the control site. Additionally, a significant increase in TAC and a significant decrease in MMP-9 levels in GCF were found in melatonin-treated sites in comparison to control sites. Conclusions. The adjunctive use of topical melatonin gel with nonsurgical periodontal therapy has potent anti-inflammatory and antioxidant activity in the treatment of grade II periodontitis patients.